THYROID FUNCTION AND MENTAL HEALTH IN CHILDBEARING AGE WOMEN - Suryati Kumorowulan; Yusi Dwi Nurcahyani; Leny Latifah; Diah Yunitawati (Media Gizi Mikro Indonesia, 2021)
Background. Thyroid dysfunction is frequently associated with psychiatric problems, such as anxiety or depression. On the other hand, thyroid dysfunction patients have little reason to be concerned about their mental health. Childbearing age women are included in the priority category because they require excellent health conditions to prepare for pregnancy and parenthood. Objective. This study aimed to investigate relationship between thyroid function (as evaluated by thyroid hormone levels and thyroid stimulating hormone (TSH) levels) with mental health in childbearing age women. Method. This study is a cross sectional study, with childbearing age women (aged 15 years and up) who are already menstruating but have not yet reached menopause. The research was conducted in Yogyakarta City and Bukittinggi City with a total sample of 487 people. This study’s independent variables were TSH and free T4 levels. The dependent variables were anxiety and depression. Other things to consider are height, body weight, and age. Blood samples had used to measure TSH and free T4 levels. All respondents were interviewed to assess whether they were depressed or anxious using the Beck Depression Inventory (BDI) and Beck Anxiety Inventory (BAI). Results. There is a significant difference in score of BAI (21.1±11,67 vs 19.7±11.18, p<0.000) and BDI (10.1±8.06 vs 9.50±7.36, p<0.000) between groups. Other results found that disfunction thyroid hormone levels (TSH <0.3 mIU/mL) was related to depression (OR 2.324 95% CI 1.072–5.041, p<0.05; AOR 2.718 95% CI 1.028–7.186, p<0.05), but not associated with anxiety. Conclusion. Thyroid dysfunction, particularly low thyroid stimulating hormone levels, has been linked to higher risk of depression in childbearing age women.